Adherence to Iron and Folic Acid Supplement and Its Associated Factors among Antenatal Care Attendant Mothers in Lay Armachiho Health Centers, Northwest, Ethiopia, 2017. (2nd June 2019) - Agegnehu, Gashaw; Atenafu, Azeb; Dagne, Henok; Dagnew, Baye
Abstract : Background . Iron deficiency is the leading nutrient deficiency globally affecting the lives of more than two billion people worldwide. Pregnant women are at higher risk of iron and folic acid deficiency due to lack of iron and folic acid or due to poor adherence. Adherence to iron and folic acid supplement is taking 65% or more of the recommended supplement, equivalent to taking the supplement at least 4 days a week during 3 months period using recording, reporting, and checking cards. Objective . The current study aimed at assessing adherence to iron and folic acid supplement during pregnancy and its associated factors among pregnant women attending antenatal care. Methods . Institution based cross-sectional study was conducted from February to March 2017. Systematic random sampling technique was used to select the study subjects. Data were collected using structured and pretested interviewer-administered questionnaire. Bivariable and multivariable logistic regression analysis were used to identify factors associated with adherence to iron and folic acid supplement among pregnant women. Adjusted odds ratio (AOR) with a 95% confidence interval (CI) was used to display the level of significance. Variables with a p-value less than 0.05 had been considered statistically significant. Result . Adherence to iron and folic acid in the current study was 28.7% with 95% CI (24.3, 33.6%). Educational status of mothers (AOR= 9.27 (95%CI: 2.47, 34.71)), educational status of husband (AOR= 0.31(95% CI: 0.11, 0.88)), family size of four (AOR=3.70(95%CI: 1.08, 12.76)), family size of five and above (AOR= 4.88(95% CI: 1.20, 19.85)), mothers who had 2500-3500 Ethiopian birr household average monthly income (AOR= 0.46(95% CI: 0.24, 0.89)), mothers who had registered at 17-24 weeks of gestation (AOR=0.40(95% CI: 0.22-0.74)) and registered at 25-28 weeks (AOR=0.20(95% CI 0.10, 0.41)), and mothers who had collected their iron and folic acid starting at first visit at first month of pregnancy (AOR= 2.42(95% CI:1.05, 5.58)) had significant association with iron and folic acid adherence. Conclusion and Recommendation . Adherence of iron and folic acid was only 28.7% in the current study. Maternal and husband education status, family size, registration time, economic status, and first visit in the first month with duration of iron and folic acid taken were factors significantly associated with adherence to iron and folic acid supplement. Therefore, anaemia prevention strategy via improved iron and folic acid supplement adherence should comprise strategies of educating pregnant mothers, improving economic status, and early antenatal care (ANC) registration that can improve adherence to iron and folic acid supplement.